Kritik Metode Hermeneutika pada Al-Qur’an: Sebuah Refleksi - Bahrul Ulum (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
The hermeneutic approach to comprehending the Qur'an is now being debated. Some believe that because it sprang historically from Christian worries about the authenticity of their sacred text, this method is unsuited for studying the Qur’an. The goal of this study is to present a historical overview of the hermeneutical approach as a technique with methodological problems, obstacles, and potential solutions when applied to interpret the Qur’an. This research is divided into three stages: data collection, data display, and conclusion. According to the study's findings, the hermeneutic approach fosters rational supremacy and treats all texts, including human works, in the same manner. Because all books are